The experience of creation and application possibilities of KÜVET - Purger, Zoltán (Acta Agraria Kaposváriensis, 2003)
During the preparations for joining the European Union, one of Hungarys important tasks is to apply a well operating real estate registration system, including owner rights and land utilization data registrations. For this up-to-date registration a digital map source can be provided by the Periphery Vector Map (Hungarian abbreviation: KÜVET), based on a converted analogue real estate registration map. This is an authoritative, digital copy of the original analogue map, considering the common state data, but because of its structure and the process of its generation, at some points it can be more accurate and can have more information than the analogue map.
Keywords: Periphery Vector Map; KÜVET